(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aimed to evaluate the etiologic factors, location and surgical technique for patients with oroantral communications (OAC).Materials and Methods: A total of 103 patients who had chronic or acute OAC and underwent surgical correction were reviewed retrospectively. The data that was recorded included gender, age, fistula location, fistula size, duration of the fistula, etiology, treatment modality, and any related complications. Results: Extraction of the first molar is associated with the highest incidence (41.75%) of OACS. Complete healing was observed in 68 patients with suturing. Surgical intervention was necessary for 35 patients. The surgical methods used for closure of the OACS included palatal-rotational flaps (PRF) in two patients, buccal flaps (BF) in 18 patients, and Bichat’s buccal fat pad (BFP) in 15 patients. Treatment in 5 cases resulted in failure, and four of these patients received a second treatment. In one case the patient refused any further surgical intervention and was treated with an obturator prosthesis. Conclusion: Location, size of the defect, and duration of the OAC are essential factors in the choice of technique. Surgeons should choose the correct approach or modify it in accordance with the characteristics of the particular OAC.